Neurocysticercosis as an Unrecognized Cause of Sudden Death: A CaseBased Study - Mohamed Izran; Ganesh Rajahan; Sneha S.; Venkatesan M.; Priyadarshee Pradhan; Arjun T. (Indian Journal of Forensic Medicine and Pathology, 2026)
Neurocysticercosis (NCC) is a leading global cause of adult-onset epilepsy and the most common parasitic infection of the central nervous system. It is caused by the larval stage of the pork tapeworm, Taenia solium, which encysts in the brain after the ingestion of eggs. While often presenting with chronic symptoms, NCC can lead to sudden, unexpected death through acute neurological or cardiac complications. Forensic awareness and a high index of suspicion are critical for identifying subclinical infections in at-risk populations. This case is based on a 43-year-old male who had multiple episodes of seizure for which he was brought to a tertiary care hospital, where he was declared brought dead. This case highlights the significance of conducting a comprehensive medicolegal death investigation, which involves interviews with relatives and a complete forensic autopsy to establish the cause and manner of death.